Single center experience with cardiac device infection: Importance of periprocedural precautions (Annals of Medical Research, 2022)
Aim: Cardiac implantable electronic devices (CIED) have been increasingly used in recent years; consequently, there has been an increment in device-related complications. In this study, we aimed to make a recommendation to the centers that can implant cardiacdevices about perioperative measures and to reinforce the role of perioperative measures in preventing cardiac device infection.Materials and Methods: The retrospective review examined the patients demographic data, medical diagnoses, operation details, echocardiographic findings, anticoagulant/ antiaggregant usement and complications (Table 1), laboratory findings and comorbidities(Table 2). No distinction was made between device types. A 90-day and a 30-day retrospective screening were performed. Patients were scheduled for follow-up visits one week and one month after the procedure. Three-month checks on telecommunication methods were performed.Results: The study included 169 people. There were 60 (35.5%) emergency department patients admitted. A pacemaker was implanted in 60 patients, an implantable cardioverter-defibrillator (ICD) in 79 patients, and a Cardiac Resynchronization Therapy (CRT) in 30 patients. The procedure time of patients with CRT implantation was significantly longer (p